2014
DOI: 10.1093/arclin/acu054
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Characteristics of Individuals Who Put Forth Inadequate Cognitive Effort in a Secondary Gain Context

Abstract: The current study sought to characterize the psychological architecture of individuals who put forth inadequate effort. The Minnesota Multiphasic Personality Inventory, 2nd Edition-Restructured Form was used to identify dimensions of psychological functioning in a mixed outpatient sample of U.S. Veterans referred for neuropsychological evaluation as part of their clinical care. After accounting for external financial incentive and symptom overreporting, results showed that the inadequate effort group (n = 23, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
(56 reference statements)
2
9
0
Order By: Relevance
“…Additionally, two items (242 and 304) that had extremely poor factor loadings were re-examined, as such poor loadings could suggest unique content related to response bias that is overly unique and would not be captured in the initial factor analyses. Content analysis of these items indicated they could plausibly fall under the domain of a positive form of response bias: a tendency to minimize faults of the self, which is consistent content in the cognitive response bias literature (e.g., Lees-Haley, 1991;Patrick & Horner, 2014). Including these two items in the scale added substantial classification accuracy (i.e., area under the curve increase from 0.70 to 0.72), and their unique content justified their inclusion, as such rationale is common in measurement research (Thorndike & Thorndike-Christ, 2010).…”
Section: Graded Response Modelsupporting
confidence: 64%
See 4 more Smart Citations
“…Additionally, two items (242 and 304) that had extremely poor factor loadings were re-examined, as such poor loadings could suggest unique content related to response bias that is overly unique and would not be captured in the initial factor analyses. Content analysis of these items indicated they could plausibly fall under the domain of a positive form of response bias: a tendency to minimize faults of the self, which is consistent content in the cognitive response bias literature (e.g., Lees-Haley, 1991;Patrick & Horner, 2014). Including these two items in the scale added substantial classification accuracy (i.e., area under the curve increase from 0.70 to 0.72), and their unique content justified their inclusion, as such rationale is common in measurement research (Thorndike & Thorndike-Christ, 2010).…”
Section: Graded Response Modelsupporting
confidence: 64%
“…From a construct standpoint, it seems logical to distinguish between PVT and SVT because reporting symptoms and characteristics on a self-report inventory is simply a different process than engaging in a performance-based cognitive task (Larrabee, 2012). As PVTs and SVTs both fall under the umbrella of response bias, it nonetheless remains plausible that they would be related, and generally research has demonstrated a weak to modest relationship between PVTs and SVTs (e.g., Gaasedelen, Whiteside, & Basso, 2017;Keiski, Shore, Hamilton, & Malec, 2015;Patrick & Horner, 2014;Temple, McBride, Horner, Taylor, 2003).…”
Section: Performance Validity and Symptom Validitymentioning
confidence: 99%
See 3 more Smart Citations